(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: Observation and analysis of cell viability in three-dimensional cultures is a prerequisite to construct functional tissue. We aimed to use a high throughput imager (NYONE® Scientific, SYNENTEC) for online observation of cell proliferation and cell death overtime to find a simple means of tracking cell health. Materials and Methods: As a model system for our investigations, we used a cell spheroid model of ovarian cancer cells. These were grown for four days to allow aggregate formation. Afterwards, they were treated with the chemotherapeutic agent paclitaxel to induce cell death. Aggregate growth was observed and documented daily using NYONE® (see Fig.1). 24 h, 48 h and 72 h after paclitaxel treatment, cell death was investigated using CellToxTM Green (Promega), respectively. In addition, an endpoint measurement using Calcein-AM and Propidium Iodide (PI) was performed after 48 h of paclitaxel treatment to detect living and dead cells, respectively. To translate this technology to innovative biofabrication methods like bioprinting, we applied the same live-dead staining assay to cells, which were printed in a hydrogel-based matrix. Results and Discussion: The continuous growth of three dimensional cell aggregates (reflecting proliferation of cells) was imaged and quantified using NYONE® and its YT-Software®. Paclitaxel treatment led to a dose-dependent increase of the CellToxTM green or PI signal (i.e. increased cell death) within the aggregates as imaged and quantified by NYONE®/YT-Software®. In bioprinted constructs, we reliably detected viable and non-viable cells. 90 % of cells appeared as Calcein-AM positive (alive). The 10 % PI-positive (non-viable) cells were predominantly located in regions, where the printed gel was slightly damaged. Conclusion: Analysis of cell viability over time can be performed in three-dimensional cell aggregates and bioprinted constructs with high-throughput imagers like NYONE®. This can be a valuable tool for quality control and thus ensure the generation of healthy tissue.